Pengaruh Produk Domestik Regional Bruto (PDRB), Tingkat Harapan Hidup, dan Harapan Lama Sekolah terhadap Indeks Pembangunan Manusia di DkI Jakarta Tahun 2010-2023 - Nur Fitria, Devita; Winanto, Asis Riat; Abas, Sayid (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
One of the important indicators for knowing the condition of successful human development in an area is HDI. DKI Jakarta is considered a province on the island of Java with a high human development index. A high HDI will provide an opportunity for a region to identify successful human development practices. This study aims to understand the influence of GRDP, life expectancy, expected years of schooling on HDI in DKI Jakarta in 2010-2023. The data used in this study is in the form of secondary data using a quantitative approach and multiple linear regression.  Data source from BPS DKI Jakarta Province. So the results of this research indicate that GRDP has a partially positive and significant impact on HDI in DKI Jakarta Province, but life expectancy and expected length of schooling partially have a negative influence with an error rate of 5% (0.05) on HDI in DKI Province Jakarta. Simultaneously, GRDP, Life Expectancy Level, and Expected Years of Schooling have an impact on HDI in DKI Jakarta Province